DEVELOPMENT OF INTEGRATED SOCIAL STUDIES LEARNING TOOLS BASED ON LOCAL WISDOM TO FOSTER CRITICAL THINKING SKILLS AND CHARACTER OF JUNIOR HIGH SCHOOL LEARNERS - Helena Rosalia Parera; Fatma Wati; Maria Elisabeth Rei Bei (Universitas Labuhanbatu, 2023)
This research is the Development of Integrated Social Studies Learning Tools Based on Local Wisdom to Develop Critical Thinking Skills and Characters of Junior High School Students (SMP). This type of research is educational development research (R&D) because it develops learning tools using the ADDIE Model. The subject of this research is a learning device based on local wisdom in improv a critical thinking power and character of students. The object of this research is the seventh-grade students of SMP Negeri 2 Ende. The methods of data collection are giving tests, questionnaires, and documentation.The results showed: 1) the results of the second test showed changes in student activity in solving questions were in the high category of 50%; 2) For Critical Thinking, the results of the N-Gain test show that the score of 57.62% is in the medium category; 3) Characters of students are in the high category of 78.6%.Keywords: Learning Devices, Local Wisdom, CharacterAbstrak Penelitian ini adalah Pengembangan Perangkat Pembelajaran IPS Terpadu Berbasis Kearifan Lokal Untuk Menumbuhkan Kemampuan Berpikir Kritis dan Karakter Peserta Didik Sekolah Menengah Pertama (SMP), Jenis Penelitian ini adalah penelitian pengembangan pendidikan (R&D) karena mengembangkan perangkat pembelajaran dengan menggunakan Model ADDIE. Subjek penelitian ini adalah Perangkat pembelajaran berbasis kearifan lokal dalam meningkatkan daya berpikir kritis dan karakter peserta didik. Yang menjadi obyek penelitian adalah anak SMP Negeri 2 Ende kelas VII. Metode pengumpulan data dengan cara Pemberian Tes, Angket serta Dokumentasi. Hasil penelitian menunjukkan : 1)hasil tes kedua menunjukan perubahan aktivitas peserta didik dalam menyelesaikan soal berada di kategori tinggi sebesar 50%; 2) Untuk Berpikir Kritis peserta didik hasil uji N-Gain hasilnya menunjukkan scorenya sebesar 57,62% berada dalam kategori sedang ; 3) Karakter Peserta Didik berada dalam kategori tinggi sebesar 78,6 %.Kata Kunci: Perangkat Pembelajaran, Kearifan Lokal, karakter